1972
DOI: 10.1111/j.1744-7348.1972.tb02944.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination of sclerotia of Botrytis tulipae, the cause of tulip fire

Abstract: S U M M A R YSclerotia of Botrytis tulipae (Lib) Lind. buried in field soil germinated mainly in winter and early spring to produce conidiophores and conidia and then decayed. Except when buried very late in the year sclerotia germinated and decayed in the season following burial.I n the laboratory, sclerotia from pure culture germinated in two ways. On sterile water-agar they formed colourless mycelium but no conidiophores; the rate of germination was greatest at 25 "C. On unsterile filter paper and on soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…Sclerotial viability was lowest at 0 cm fov sclerotia of B. cinerea and B. tulipae. This contrasts with the results of Coley-Smith & Javed (1972), who found greater recovery and viability for B. tulipae sclerotia at the surface than for those buried at depths of 7-5, 15 0 or 23 0 cm during the 18-month monitoring period. Average monthly soil temperatures for the different soil depths are presented in Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Sclerotial viability was lowest at 0 cm fov sclerotia of B. cinerea and B. tulipae. This contrasts with the results of Coley-Smith & Javed (1972), who found greater recovery and viability for B. tulipae sclerotia at the surface than for those buried at depths of 7-5, 15 0 or 23 0 cm during the 18-month monitoring period. Average monthly soil temperatures for the different soil depths are presented in Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Epidemics of B. tulipae are able to start from over-wintering sclerotia in crop debris or soil, or by latent infections in bulbs. In view of the long crop rotation schemes and the observation that sclerotia cannot survive in soil for more than two growing seasons, the most probable primary sources of inoculum are the latent infections in bulbs (Coley-Smith & Javed, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Observations made at 2-4 weeks intervals in the autumn showed that growth of the pathogen in the outer scale starts soon after planting. If the fungus, which can originate from various sources (Doornik and Bergman, 1971, 1973, 1974Coley-Smith and Javed, 1972), spreads strongly through the scales after planting, the first symptoms on the tunics of offspring bulbs may be found as early as several weeks before the plant flowers. Usually, however, these symptoms are seen after flowering, when the young bulbs start to grow vigorously.…”
Section: Sources and Modes Of Infection During The Gro Wing Periodmentioning
confidence: 99%
“…) Lind from various sources, viz. conidia present on the bulb surface (Doornik and Bergman, 1974), mycelium present in the brown tunic or in local lesions in the outer scale (Price, 1970;Doornik and Bergman, 1971), or inoculum in the soil (Coley-Smith and Javed, 1972;Doornik and Bergman, 1974). However, there is no information in the literature on the mode and source of infection of the offspring bulbs during the growth period and during storage after harvest.…”
Section: Introductionmentioning
confidence: 96%